2008
DOI: 10.1103/physrevb.78.235201
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure ofNaxCu1xIn5S8compoun

Abstract: The aim of the present work is to complete a preliminary study concerning the electronic band structure investigations of Na x Cu 1−x In 5 S 8 compounds with 0 Յ x Յ 1, which are expected to be formed at the Cu͑In, Ga͒Se 2 / In 2 S 3 interface. The band structure calculations demonstrate that for the compounds containing both Na and Cu, as the Cu content increases the band gap tends to decrease, and x-ray photoemission spectroscopy measurements show that this variation is mainly due to valence-band-maximum shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Speculated shifts of the VBM and CBM are indicated with arrows and gray bars in Figure B). We show a slightly larger gray bar for the VBM since it is predominantly influenced by selenium and copper and hence expected to show the more pronounced change. Figure summarizes the results of this section.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Speculated shifts of the VBM and CBM are indicated with arrows and gray bars in Figure B). We show a slightly larger gray bar for the VBM since it is predominantly influenced by selenium and copper and hence expected to show the more pronounced change. Figure summarizes the results of this section.…”
Section: Resultsmentioning
confidence: 82%
“…With x‐ray photoelectron spectroscopy (XPS), it was found that the copper diffusion shifts the valence band maximum (VBM) of the buffer towards the Fermi level, and optical measurements suggest a decrease in the band gap . However, only a few publications report on sodium‐doped indium sulfide buffer layers . The incorporation of sodium into the In 2 S 3 buffer layer is expected to increase its band gap as a function of the sodium content, from ~2.0 to 2.2 eV (for vapor deposition) to ~2.9 eV, the latter being significantly larger than the CdS band gap .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the corresponding solar‐cell devices exhibit a Cu‐depleted/In‐rich region on the absorber side of the absorber/buffer interface and a Cu‐ (as well as Na‐ and Ga‐) containing In 2 S 3 buffer. As Cu and Na occupy the same sites of the In 2 S 3 crystal structure 136, 137, the amount of Cu diffusing into the buffer also depends on the amount of Na available on the Cu(In,Ga)(S,Se) 2 surface prior to the buffer deposition 132, 138.…”
Section: Interface Effectsmentioning
confidence: 99%
“…A complementary explanation could be the inclusion of sodium in the spinel CuIn 5 S 8 phase, resulting in (Na,Cu)In 5 S 8 at the surface of the absorber layer. This latter has a lower electron affinity than the former 35 ; therefore, it likely better aligns with the chalcopyrite and CdS conduction bands, 36,37 which reduces the absorber/buffer interface cliff losses. EQE measurements (see Figure 5) support this latter hypothesis.…”
Section: Resultsmentioning
confidence: 99%